Schools and Styles of Anthropological Theory
1 online resource (xli, 521 pages)
Keywords: "From the inception of the discipline in the 19th century, great ideas have always inspired and guided anthropologists when conducting their research amongst people all over the world. Such great ideas are born from the social and political contexts of their creators, and the challenge for scholars of anthropology today is to understand the value these ideas bring to modern fields of enquiry. Each chapter in this textbook has been written to provide a thorough yet engaging introduction to one particular theoretical school and style. These chapters build up to a coherent and well-organised picture of the history and contemporary shape of anthropological theory. Beginning with an introduction which reflects on the substantive themes which tie the chapters together, the book ends with an afterword by Marilyn Strathern reflecting on broader themes in the use of history and anthropological concepts. Presenting a detailed and comprehensive critical introduction to the most salient areas of the field, this book is essential reading for all undergraduate students undertaking a course on anthropological theory or the history of anthropological thought. It will also be useful reading for students of social and cultural anthropology, sociology, and human geography, and those enrolled in an anthropology course during their postgraduate degree with no background in the field."--Provided by publisher.